2018
DOI: 10.3390/ijms19113349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Skin Gene Expression by Different Blends of Plant Extracts with Implications to Periorbital Skin Aging

Abstract: Since the skin is the major protective barrier of the body, it is affected by intrinsic and extrinsic factors. Environmental influences such as ultraviolet (UV) irradiation, pollution or dry/cold air are involved in the generation of radical oxygen species (ROS) and impact skin aging and dermal health. Assessment of human skin gene expression and other biomarkers including epigenetic factors are used to evaluate the biological/molecular activities of key compounds in cosmetic formulas. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, other authors have shown that lignins present in S. chinensis extracts, such as deoxyschisandrin and Schizandrin B, can block Cox-2 cyclooxygenase, IL-6 interleukin and the IL-18 interleukin signaling pathway, thereby protecting skin cells from UVB radiation damage and greatly reduce the intracellular level of reactive oxygen species. Additionally, Schizandrin B may regulate the activity of superoxide dismutase (SOD), significantly reduce the production of many inflammatory factors, and lower the expression level of matrix metalloproteinase-1 (MMP-1), thus inhibiting the collagen degradation process [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other authors have shown that lignins present in S. chinensis extracts, such as deoxyschisandrin and Schizandrin B, can block Cox-2 cyclooxygenase, IL-6 interleukin and the IL-18 interleukin signaling pathway, thereby protecting skin cells from UVB radiation damage and greatly reduce the intracellular level of reactive oxygen species. Additionally, Schizandrin B may regulate the activity of superoxide dismutase (SOD), significantly reduce the production of many inflammatory factors, and lower the expression level of matrix metalloproteinase-1 (MMP-1), thus inhibiting the collagen degradation process [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…There are two published studies (by the same group) that demonstrate its efficacy in the prevention of chronological skin aging-it was proposed that a decrease in cell turnover time produces this effect [61,62]. In another study looking at cell proliferation and dermal structural components, an increase in the production of growth factors, signaling molecules, structural biomarkers, and oxidative stress indicators was observed for a blend of Narcissus tazetta bulb extract and Schisandra chinensis fruit extract [63].…”
Section: Cosmetics and Dermatology In Ancient Greece And Romementioning
confidence: 99%
“…For example, citrus sinensis peel extract (CSPE) nanoformulation ( Amer et al, 2021 ), extracts and bioactive compounds derived from seaweed ( Pangestuti et al, 2021 ), and atractyligenin ( Xuan et al, 2019 ) were reported to suppress ROS by activating the MAPK pathway. As such, CSPE nanoformulations ( Amer et al, 2021 ), BlendE, BlendIP ( Namkoong et al, 2018 ), and tannic acid ( Daré et al, 2020 ) are associated with either an increase in antioxidative enzyme expression or a decrease in ROS generation. Second, the regulation of inflammatory responses is beneficial to anti-aging therapy, such as that with a mixture of marigold and rosemary extracts, CSPE nanoformulation ( Amer et al, 2021 ), bamboo leaf flavonoids (BLF) ( Gu et al, 2022 ), and ursolic acid ( Samivel et al, 2020 ).…”
Section: Mechanisms Underlying Skin Agingmentioning
confidence: 99%